Genetic Diversity in Some Sesame (Sesamum indicum L.) Accessions Detected by Agro-morphological Characters and RAPD Markers* - Ibrahim, Elshiekh Awadelkarim; Abdalla, Abdelwahab Hassan; Saker, Mahmoud Mohamed (University of Khartoum Journal of Agricultural Sciences, 2023)
Agro-morphological and Randomly Amplified Polymorphic DNA (RAPD) markers were used to determine the diversity and relationships among 25 accessions of sesame from Sudan. Data on 16 agro-morphological characters were collected from a field experiment, carried out at Shambat for three consecutive seasons (2006-2008) and subjected to the procedure of cluster analysis. The results showed that cluster analysis, based on Euclidean distance, of the agro-morphological characters grouped the 25 sesame accessions into seven clusters. Application of RAPD markers generated 48 bands with a 97.9% polymorphism. A dendrogram constructed from the RAPD data classified the 25 sesame accessions into eight major clusters. It was concluded that for efficient estimation of genetic diversity and interrelationships among sesame accessions, information obtained from both agro-morphological characters and RAPD should be combined.